Reasons to give: free market 2.0 / Nazima Versav Kudus... [et al.] - Versay Kudus, Nazima; Razali, Wan Noorli; Desa, Melati; Seng, Hui Zanne; Abdul Halim, Muhammad Aiman (Academy of Language Studies, 2022)
It is simply a waste to just see good things piled up in a cupboard while the owner tries to figure out what to do with them. David Khalil is correct when he says that true happiness is when we share the things that we love. This has motivated the UiTM Cawangan Pulau Pinang Free Market committee to organise Free Market 2.0 from 2-3 December 2021 with the theme 'Gol & Gincu’. 10 faculties and departments participated in the event, among them the Academy of Language Studies (ALS). The objective of the event was to donate previously owned goods for needful individuals. ALS’ committee comprises Noorli, Nazima, Melati, Zanne, Aiman, Azli, Noraziah, Marni, and Dr. Ilianis. These committee members were either donors of items such as toys, clothing, kitchenware and electrical appliances or in charge of manning the booth. A lucky draw was also held at ALS’ booth. Take-home items consisted of stationeries such as notepads, pens and pencils. In order to attract donor recipients, Marni had conducted head-scarf wearing demonstrations. Due to the overwhelming support, by 1.00 PM, almost all donated items were cleared. The committee would like to thank those who had participated and made it an astounding success